STUDI PERILAKU STRUKTUR GEDUNG 10 LANTAI MENGGUNAKAN COUPLED SHEAR WALL DENGAN SISTEM COUPLING BEAM TERHADAP BEBAN GEMPA BERDASARKAN SNI 1726-2019 - Octavia Eka Putri; Muhamad Ryanto (Sistem Infrastruktur Teknik Sipil (SIMTEKS), 2022)
Comparison of behavior in a 10 storeys building structure without shear wall and using the coupled shear wall of the coupling beam system located in the city of Bandung. The two structures are designed as apartment buildings with a Special Moment Resistant Frame System and dual Special Structural Wall System. The location of the earthquake zone using spectrum response analysis procedures is included in risk category II. The soil site class in the area includes medium soil (SD).The results of the analysis of the two structures, the value of the y direction mode 1 period from the ETABS software output is 2.14 seconds for structures without shear walls and 1,21 seconds for the coupled shear wall structure of the coupling beam system. Therefore that the structure without shear wall is 76% more flexible than the structure using shear wall. The structure using shear wall is designed to withstand earthquake base shear with a value obtained of 5292.3 kN, 78% greater than the structure without shear wall which only has a base shear value of 2969.84 kN. In addition, the story drift that occurs in the coupled shear wall structure of the coupling beam system 13% stiffer than the structure without shear wall.Therefore, the coupled shear wall structure of the coupling beam system has high ductility and tends not to be brittle so that it is able to withstand base shear, lateral forces caused by earthquakes